The concept of non-contractual obligations in inheritance law: international legal experience - Рябоконь, Євген Олександрович; Рябоконь, Є. О.; Рябоконь, Евгений Александрович; Riabokon, Yevhen O.; Riabokon, Ievgen; Фурса, Євген Євгенович; Фурса, Є. Є.; Фурса, Евгений Евгеньевич; Fursa, Yevhen Ye.; Цибульська, Ольга Юріївна; Цибульська, О. Ю.; Цибульская, Ольга Юрьевна; et al. (Editorial Primmate S. A. S., 2021)
The article is devoted to the study and analysis of such areas of civil law as non-contractual structures, within the inheritance law of individual European Union countries, the emergence, development and implementation of such structures in regulations governing the inheritance procedures of countries such as Poland, Czech Republic, Republic of Lithuania and the Republic of Latvia. The purpose of the study in the monograph is a comprehensive analysis of the nature and specifics of legal and doctrinal bases of regulation and practice of non-contractual constructions in the inheritance law of individual EU countries (Poland, Czech Republic, Lithuania, and Latvia). As a result of the study the concept of non-contractual constructions of inheritance law is formed in the work. The types of non-contractual constructions, first of all their dialectical classification, architecture and place in the system of inheritance law are singled out and analyzed. An analysis of their identification and separation in different states, depending on the legal family, traces the integrity of the fundamental structure of knowledge about the obligatory rights of the testator within the will, heirs and beneficiaries in their biocentric expression and in the context of social ties. Emphasis is placed on rethinking and solving some problems in inheritance law, from the point of view of new world realities.

Стаття присвячена дослідженню та аналізу такого напряму цивільної правової науки, як недоговірні конструкції, в рамках спадкового права окремих країн Європейського Союзу, виникненню, розвитку та реалізації таких конструкцій в нормативно-правових актах, які врегульовують процедури спадкування таких країн як Республіка Польща, Чеська Республіка, Литовська Республіка та Латвійська Республіка. Мета дослідження в монографії полягає комплексному аналізі природи і специфіки нормативно-правових та доктринальних основ регламентації та практики реалізації̈ недоговірних конструкцій в спадковому праві окремих країн ЄС (Республіки Польщі, Чеської Республіки, Литовської Республіки та Латвійської Республіки). В результаті проведеного дослідження сформовано концепцію недоговірних конструкцій спадкового права. Виокремлено та проаналізовано види недоговірних конструкцій, насамперед їх діалектичної класифікації, архітектоніки та місця в системі спадкового права. Зроблено аналіз щодо їх ідентифікації та відокремлення у різних державах, залежно від правової сім’ї, прослідковано цілісність фундаментальної структури сфери знань щодо зобов’язальних прав заповідача в межах заповіту, спадкоємців та вигодонабувачів у їх біоцентричному вираженні та у контексті соціальних зв’язків. Зроблено акцент на переосмисленні та вирішенні деяких проблем у спадковому праві, під кутом зору нових світових реалій.
Riabokon I. The concept of non-contractual obligations in inheritance law: international legal experience / I. Riabokon, Ye. Fursa, O. Tsybulska, A. Goncharova, O. Kryzhevska // Amazonia Investiga. – Vol. 10. – Iss. 45. – Editorial Primmate S. A. S., 2021. – P. 221-229.
Keywords: non-contractual constructions; inheritance; inheritance law; will; heir; позадоговірні конструкції; спадкування; спадкове право; заповіт; спадкоємець; Research Subject Categories::LAW/JURISPRUDENCE